2012
DOI: 10.5751/es-04520-170126
|View full text |Cite
|
Sign up to set email alerts
|

Public Preferences Across Europe for Different Forest Stand Types as Sites for Recreation

Abstract: Traditional policies for water resources management and wetland conservation are often based on command-andcontrol approaches. The latter tend to drive the human-wetland-water system into pathological states, characterized by more vulnerable ecosystems and rigid institutions for governance. The overcoming of these states may rest in the development of flexible and adaptive institutional regimes that rely on adaptive governance and management. Because past factors might constrain the implementation of more flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 66 publications
2
22
0
2
Order By: Relevance
“…However, this corroborates the findings of Edwards et al. () that broadleaves and mixtures are only marginally preferable to conifers and monocultures, respectively. Furthermore, although these preferences are generally found across Europe, results are mixed (Felton et al., ; Gundersen & Frivold, ; Termansen et al., ), so it is perhaps not particularly surprising that there is not a more dramatic distinction between broadleaves and conifers or between mixtures and monocultures.…”
Section: Discussionsupporting
confidence: 92%
“…However, this corroborates the findings of Edwards et al. () that broadleaves and mixtures are only marginally preferable to conifers and monocultures, respectively. Furthermore, although these preferences are generally found across Europe, results are mixed (Felton et al., ; Gundersen & Frivold, ; Termansen et al., ), so it is perhaps not particularly surprising that there is not a more dramatic distinction between broadleaves and conifers or between mixtures and monocultures.…”
Section: Discussionsupporting
confidence: 92%
“…Non-economic assessments of ecosystem services have rapidly advanced in recent years (e.g., Fagerholm et al, 2012, Klain and Chan, 2012, Sherrouse et al, 2011and Sherrouse et al, 2014. They typically engage local stakeholders in the identification and quantification of a broad range of 'social' and 'cultural' values for ecosystem services using participatory techniques such as Delphi surveys (e.g., Edwards et al, 2012), scenario analysis (e.g., Maes et al, 2012), Q method (e.g., Hodge, 2012 andKerr andSwaffield, 2012), multi-criteria analysis (e.g., Karjalainen et al, 2013, Nahuelhual et al, 2013and Verburg et al, 2014 and public participation GIS (e.g., Brown et al, 2011, Raymond et al, 2009, Sherrouse et al, 2011, Sherrouse et al, 2014and Van Riper et al, 2012. While terms such as 'social' and 'cultural' value have been fuzzy, difficult to define and applied in different contexts (Ives and Kendal, 2014), the non-economic ecosystem services literature has tended to conceive social values expressed in non-monetary terms as a more pluralistic and heterogeneous alternative to economic conceptions of value .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, various case studies have demonstrated that European people prefer broadleaved or mixed forest and often consider coniferous stands as less natural; that could negatively influence WTP values (Mill et al 2007;Edwards et al forthcoming). Lower values are observed for southwestern and southeastern parts of France, while upper values are observed for northeastern and Paris areas.…”
Section: Discussionmentioning
confidence: 99%